PENGARUH MEDIA e-LEARNING BERBASIS WEBLOG PADA PEMBELAJARAN MODEL KOOPERATIF TIPE TPS (THINK PAIR SHARE) TERHADAP HASIL BELAJAR KIMIA SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR - Anna Juniar; Ika Trisna Br Karo S; Hafni Indriati Nasution; Nurmalis Nurmalis (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract This research was purposed to look at the influence of e-learning based weblog implementation toward the increasing of student’s achievement on subject of atom structure and periodict unsure system. The population of research was all students of XI IPA SMAN 3 Medan which consisted of 9 classes with total of 414 students. By using random sample, 2 classes with total of 80 students was used as sample such that gotten class of 1st experiment was e-learning based weblog with instructional model of TPS cooperative type and class of 2nd experiment was not e-learning based weblog with instructional model of TPS cooperative type. The percentage of student’s achievement was increasing by using e-learning based weblog toward the teaching and learning with instructional model of TPS cooperative type was 77.920% and without it was 66.200%. By using data analysis, t-statistics was 6.267 than t-table was 1.994 where α = 0.05 and dk = 78 such that t-statistics > t-table. So, Ha was accepted and could be concluded that student’s achievement by using e-learning based weblog implementation using instructional model of TPS cooperative type was higher than the student’s achievement without it.  Kata Kunci : e-Learning, Weblog, Think Pair Share (TPS)